2022
DOI: 10.1186/s13195-022-00992-y
|View full text |Cite
|
Sign up to set email alerts
|

APOE ε4, Alzheimer’s disease neuropathology and sleep disturbance, in individuals with and without dementia

Abstract: Background Apolipoprotein E epsilon 4 (APOE-ε4) carrier status is an established risk factor for Alzheimer’s disease (AD) dementia. It has also been linked with sleep disturbance in healthy older adults and increased insomnia risk. This association may be driven by the effect of APOE-ε4 on AD pathological change, itself associated with sleep abnormalities. To assess this relationship, we have evaluated post-mortem neuropathological findings in patients with and without cognitive impairment and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 91 publications
1
8
0
1
Order By: Relevance
“…Previous findings have been mixed in linking the APOE polymorphism to sleep disturbances at a single time point . Here, we demonstrate that the APOE ε4 allele (vs ε3/ε3) was associated with greater SWS loss.…”
Section: Discussionmentioning
confidence: 47%
“…Previous findings have been mixed in linking the APOE polymorphism to sleep disturbances at a single time point . Here, we demonstrate that the APOE ε4 allele (vs ε3/ε3) was associated with greater SWS loss.…”
Section: Discussionmentioning
confidence: 47%
“…CPAP treatment may delay the progression of cognitive impairment, and the duration of CPAP is critical for improving the therapeutic effect of cognitive impairment in OSA patients [35, 36]. The apolipoprotein epsilon 4 ( APOEε4 ) allele is the strongest genetic risk factor for late-onset AD, and the effect of APOEε4 on sleep quality may contribute to sleep disturbances in individuals at increased risk for dementia [37]. In addition, a study showed that mutations in natural short sleep genes can reduce the AD pathology in animals, which opens a new path for the treatment of neurodegenerative diseases such as sleep deprivation-induced AD [38].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, APOEε4 may affect sleep by mechanisms that are both dependent and independent of AD pathological change. 97…”
Section: Molecular Mechanisms Of Admentioning
confidence: 99%